2017
DOI: 10.1111/ele.12740
|View full text |Cite
|
Sign up to set email alerts
|

Interaction rewiring and the rapid turnover of plant–pollinator networks

Abstract: Whether species interactions are static or change over time has wide-reaching ecological and evolutionary consequences. However, species interaction networks are typically constructed from temporally aggregated interaction data, thereby implicitly assuming that interactions are fixed. This approach has advanced our understanding of communities, but it obscures the timescale at which interactions form (or dissolve) and the drivers and consequences of such dynamics. We address this knowledge gap by quantifying t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
377
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 293 publications
(402 citation statements)
references
References 54 publications
(56 reference statements)
22
377
2
1
Order By: Relevance
“…While previous studies based on temporal dynamics have focused on the seasonal turnover of interactions ( e.g. Olesen et al ; CaraDonna et al ), this is the first study to provide a quantitative description of the seasonal changes in the metrics of a plant–visitor interaction network. To our knowledge, it is also the first study to assess the effect of temporal data aggregation on quantitative network descriptors.…”
Section: Discussionmentioning
confidence: 97%
“…While previous studies based on temporal dynamics have focused on the seasonal turnover of interactions ( e.g. Olesen et al ; CaraDonna et al ), this is the first study to provide a quantitative description of the seasonal changes in the metrics of a plant–visitor interaction network. To our knowledge, it is also the first study to assess the effect of temporal data aggregation on quantitative network descriptors.…”
Section: Discussionmentioning
confidence: 97%
“…It is alarming that during disassembly processes following habitat loss competitive release seems to promote rewiring of generalized rather than specialized interactions, which may decrease resilience to environmental change (CaraDonna et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…In pollination networks, for example, studies have suggested that it will be essential to know the match between plant and pollinator traits in order to understand how the interaction network works, as well as for predicting changes in their structure (Garibaldi et al., ; Maglianesi, Blüthgen, Böhning‐Gaese, & Schleuning, ), but see Bartomeus, Cariveau, Harrison, and Winfree (); CaraDonna et al. (). Likewise, results from experiments have shown that body mass can largely influence biotic interactions, in particular predator–prey links (Brose, ; Brousseau, Gravel, & Handa, ; Gravel et al., ).…”
Section: Introductionmentioning
confidence: 99%